PGRMC1 and PGRMC2 in uterine physiology and disease - Pru, James K.; Clark, Nicole (Frontiers in Neuroscience, 2013)
It is clear from studies using progesterone receptor (PGR) mutant mice that not all of the actions of progesterone (P4) are mediated by this receptor. Indeed, many rapid, non-classical P4 actions have been reported throughout the female reproductive tract. Progesterone treatment of Pgr null mice results in behavioral changes and in differential regulation of genes in the endometrium. Progesterone receptor membrane component (PGRMC) 1 and PGRMC2 belong to the heme-binding protein family and may serve as P4 receptors. Evidence to support this derives chiefly from in vitro culture work using primary or transformed cell lines that lack the classical PGR. Endometrial expression of PGRMC1 in menstrual cycling mammals is most abundant during the proliferative phase of the cycle. Because PGRMC2 expression shows the most consistent cross-species expression, with highest levels during the secretory phase, PGRMC2 may serve as a universal non-classical P4 receptor in the uterus. While the functional importance of PGRMC1/2 in the uterus remains to be fully explored, accumulating evidence suggests that disruption in PGRMC1/2 expression correlates with uterine disease. In this review we will summarize what is known about PGRMC1/2 in uterine physiology and we will provide examples of disrupted expression of these genes in uterine disease states.